Kajian Konsentrasi Ekstrak Etanol Daun Karamunting (Melastoma malabathricum L) dalam Sediaan Krim terhadap Sifat Fisik dan Aktivitas Antioksidan: Study of Karamunting Leaves (Melastoma malabathricum L) Ethanol Extract Concentration in Cream Formulation on Physical Properties and Antioxidant Activity - Rohani Rohani; Dewi Mayasari; Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Karamunting leaves (Melastoma malabathricum L) have been widely used in traditional medicine due to various pharmacological activities related to its secondary metabolites, namely, flavonoids and tannins. The general objective of this research is to obtain the concentration of ethanol extract of karamunting leaves in a cream formulation that gives excellent physical properties and has antioxidant activity. The result showed extract antioxidant activity was in a very strong category with an IC50 value of 6,927 ppm. Cream with the best antioxidant activity in this study was F3 (3%) because it had the highest antioxidant activity in a strong category with an IC50 value of 60.38 ppm and had the best physical properties compared to F0 (negative control), F1 (1%), F2 (2%), and F4 (vitamin E). The freeze-thaw physical stability test showed that all formulas F0, F1, F2, F3, and F4 had good physical stability, namely, the physical properties did not differ significantly between before and after freeze-thaw for 5 cycles (p>0.05).